Hélio Oiticica : a grande ordem da cor - Santos, Nívia Valéria dos (2012)
This paper, "Hélio Oiticica: the supreme order of color" analyzes the spatial distribution of color in the artistic and experimental trajectory of this artist between the years 1955-1965. Helio Oiticica built a poetic way in which the color was a constant